Qualidade de vida, fatores sociodemográficos, clínicos e subjetivos em adultos com feridas de difícil cicatrização - Jacon, João Cesar (Universidade Federal de São Carlos, 2024)
To assess the quality of life and sociodemographic, clinical, and subjective factors (depression, anxiety, stress, self-esteem, self-efficacy, self-care, and pain) in adults with hard-to-heal wounds. Methodology: A correlational, descriptive, cross-sectional study with a quantitative approach. Data were collected in two municipalities in the state of São Paulo. The sample consisted of 116 patients. The following instruments were used to collect the data: the Depression, Anxiety and Stress Scale - Short Form (DASS-21), the Appraisal of Self-Care Agency Scale (ASA-A), the Rosenberg Self-Esteem Scale (RAS), the Perceived General Self-Efficacy Scale (The General Self-Efficacy Scale) and the Freiburg Life Quality Assessment-Wound (FLQA-Wk), by which the results were presented considering relative and absolute frequencies, as well as measures of central tendency. For inferential statistical analysis, the following tests were used: correlation (Spearman and Chi-square), association and comparison (Mann-Whitney or Kruskal Wallis), and the Bonferroni post-test. CAAE: 63323822.9.0000.5504. Results: DASS-21, depression (68.1%), anxiety (76.7%), and stress (71.6%) between normal and mild, 43.1% optimal abilities to carry out self-care. 50% of the patients reported pain in the wound during the interview, with a median of 1.0 (IIQ 0-8.0), and the median time the wound had existed was 52 months (IIQ 17.0-204.0). In the quality-of-life assessment, the median was 10.7 (IIQ 6.4–13.6), the psychological well-being domain represents a state of a better quality of life (median 1.0 and IIQ 0.3–1.5), and the daily life (median 2.4 and IIQ 1.4–3.2) and treatment (median 2.4 and IIQ 1.5–3.0) domains represent domains with the worst quality of life. The overall score for self-esteem was a median of 31.5 (IIQ 26.0–34.8) and for self-efficacy, a median of 4.3 (IIQ 3.2–4.8). Conclusion: Patients with difficult-to-heal wounds had a poor overall quality of life and were associated with the presence of pain at the time of the interview, female gender, insufficient income, not practicing physical activity, and wounds of vasculogenic etiology, as well as symptoms of moderate depression. Wound pain during the interview was correlated with the number of wounds that were difficult to heal and was associated with symptoms of mild depression. Patients with vasculogenic wounds complained of greater intensity. Symptoms of moderate depression were identified in single people, and low schooling was associated with depressive symptoms. Anxiety, depression, stress, low self-esteem, and a low perception of self-efficacy were more evident in women with wounds that were difficult to heal. Physical activity and schooling had a negative influence on perceived self-efficacy. Elderly people with chronic wounds have a lower capacity for self-care, lower self-esteem, and a poorer perception of self-efficacy.

Evaluar la calidad de vida, factores sociodemográficos, clínicos y subjetivos (depresión, ansiedad, estrés, autoestima, autoeficacia, autocuidado y dolor) en adultos con heridas de difícil cicatrización. Metodología: Estudio correlacional, descriptivo, transversal, con enfoque cuantitativo. La recolección de datos se realizó en dos municipios del estado de São Paulo. La muestra estuvo compuesta por 116 pacientes. Para la recolección de datos se utilizaron los siguientes instrumentos: Escala de Depresión, Ansiedad y Estrés – Forma Corta (DASS-21), Escala de Evaluación de la Agencia de Autocuidado (ASA-A), Escala de Autoestima de Rosenberg (EAR), Escala de Autocuidado. Escala de Eficacia General Percibida (The General Self-Efficacy Scale) y para la calidad de vida Freiburg Life Quality Assessment–Wound (FLQA-Wk), a través de la cual se presentaron los resultados considerando frecuencias relativas y absolutas, así como medidas de tendencia central. Para el análisis estadístico inferencial se utilizaron las siguientes pruebas: correlación (Spearman y Chi-cuadrado), asociación y comparación (Mann Whitney o Kruskal Wallis) y el postest de Bonferroni. CAAE: 63323822.9.0000.5504. Resultados: DASS-21, depresión (68,1%), ansiedad (76,7%) y estrés (71,6%) entre normal y leve, 43,1% excelentes habilidades para realizar el autocuidado. El 50% de los participantes refirió dolor en la herida durante la entrevista, con una mediana de 1,0 (IIQ 0-8,0), la mediana de tiempo que estuvo la herida en meses fue de 52 (RIQ 17,0-204, 0). En la valoración de la calidad de vida la mediana fue 10,7 (IIQ 6,4-13,6), el dominio bienestar psicológico representa un estado de mejor calidad de vida (mediana 1,0 y IIQ 0,3-1,5), la vida diaria (mediana 2,4 y Los dominios IIQ 1,4-3,2) y tratamiento (mediana 2,4 y IIQ 1,5-3,0) representan dominios con la peor calidad de vida. La puntuación de autoestima general, mediana 31,5 (IIQ 26,0-34,8) y para autoeficacia, mediana 4,3 (IIQ 3,2-4,8). Conclusión: Los participantes con heridas de difícil cicatrización presentaron una calidad de vida general regular asociada a: la presencia de dolor al momento de la entrevista; al sexo femenino; ingresos insuficientes, hábito de no práctica de actividad física y heridas de etiología vasculogénica, así como síntomas de depresión moderada. El dolor en la herida, durante la entrevista, se correlacionó con el número de heridas de difícil cicatrización y se asoció con síntomas de depresión moderada, y en pacientes con heridas vasculogénicas hubo quejas de mayor intensidad. Se identificaron síntomas de depresión moderada en los solteros, del mismo modo que un bajo nivel educativo se asoció con síntomas depresivos. Tanto la ansiedad como la depresión, el estrés, la baja autoestima y la baja percepción de autoeficacia son más evidentes en mujeres con heridas de difícil cicatrización. La práctica de actividad física y educación influyó negativamente en la percepción de autoeficacia. Las personas mayores con heridas crónicas tienen menor capacidad de autocuidado, menor autoestima y peor percepción de autoeficacia.
Quality of life, sociodemographic, clinical and subjective factors in adults with difficult-healing wounds
Keywords: Feridas de dificil cicatrização; Qualidade de vida; Dor; Ansiedade; Depressão; Estresse; Autocuidado; Autoestima; Autoeficácia; Enfermagem; Hard-to-heal wounds; Quality of life; Pain; Anxiety; Depression; Stress; Self-care; Self-esteem; Self-efficacy; CIENCIAS DA SAUDE::ENFERMAGEM